Character strengths, social anxiety, and physiological stress reactivity - Li,Tingting; Duan,Wenjie; Guo,Pengfei (PeerJ, 2017)
In this paper, the effects of character strengths on the physiological reactivity to social anxiety induced by the Trier Social Stress Task were reported. On the basis of their scores in the Chinese Virtues Questionnaire, 30 college students were assigned to either high- (n = 15) or low-character-strength (n = 15) groups. Their psychological stress and physiological data across three laboratory stages (namely, baseline, stress exposure, and post-stress) were collected. Results indicated that individuals with high character strengths exhibited rapid cardiovascular recovery from baseline to post-stress even if high- and low-character-strength groups showed similar patterns of cardiovascular arousal in response to the stress at baseline and stress exposure. These results prove that character strengths are stress-defense factors that allow for psychological and physiological adaptation to stress.
Keywords: Stress; Physiological recovery; Social anxiety; Character strengths; Positive psychology